A new species of Syngonium sect. Syngonium (Araceae) from Chiapas, Mexico - Jiménez, Pedro Díaz; Pérez-Farrera, Miguel Ángel; Croat, Thomas B.; Martínez-Martínez, Mauricio Gerónimo; Méndez, Gaspar Moreno; Hentrich, Heiko; Aguilar-Rodríguez, Pedro A. (Phytotaxa, 2026)
The genus Syngonium is represented in Mexico by ten species, seven of which are registered for the state of Chiapas. During fieldwork between 2020 and 2025 in Berriozabal, Chiapas, we discovered an undescribed species of Syngonium sect. Syngonium that is morphologically similar to S. neglectum, but differing from that species in having one or two inflorescences per axil, glaucous stems and spathe tube, a spathe blade almost twice as long as the staminate portion of the spadix, staminate flowers retuse at the apex, glaucous immature infructescence and the spathe not persistent in mature fruits.